Study on passive building design features suitable for Sarawak's Housing - Azrul, Bin Zulwali Kifli. (Universiti Malaysia Sarawak, (UNIMAS), 2012)
he main objective of this study is to assess and compare the impact of adding in passive design features, focusing on the orientation, roof pitch and roofing materials, to a 'base model' house based on an existing structure, on the indoor air temperature and elative humidity, for the each of the rooms. The test is conducted with the help of EnergyPlus software. The software is first validated by comparing the generated data with a real on-site data. On-site data were collected by measuring the air temperature and relative humidity, using two instruments, namely the data logger and relative humidity anemometer, for a set period, in one of the rooms of the selected house. The ideal orientation in terms of comfort is first identified, by testing one of the materials on vaious roof pitches, through all the major orientation. The base model is then tested on all the combinations of roof pitches and roofing materials, and the indoor air temperature and relative humidity are measured and recorded.